Current Situation, Trend Prediction and Development Suggestions for the Export of Chinese Automobiles - Gao, Tianfang; Dong, Bo; Zhu, Qing (International Journal of Global Economics and Management, 2024)
In recent years, promoting the high-quality development of the manufacturing industry has become a major economic development strategy in China. High-quality development in automobile trade has also achieved certain results, with export volumes stabilizing and increasing. Market layout and product structure continue to be optimized, and the international competitiveness and influence of Chinese brands are constantly improving. Since 2022, Chinese automobile brands have performed well in the global automobile market, with multiple breakthroughs in overseas exports. Different from the past focus on a single market, Chinese brand automobiles are accelerating their globalization, becoming a new choice for consumers. For many domestic brands, what the era of conventional vehicles could not accomplish, everything is possible in the new energy era. Industry experts indicate that by seizing the opportunities presented by the transformation of the automobile industry towards new energy and intelligent connected vehicles, and by enhancing the independent and controllable levels of the industry and supply chain, Chinese automobile exports are expected to reach new heights.